2003
DOI: 10.1063/1.1604465
|View full text |Cite
|
Sign up to set email alerts
|

Indication of hysteresis in AlMnN

Abstract: AlN films grown by gas-source molecular beam epitaxy were doped with different levels of Mn during growth. High resolution x-ray diffraction characterization revealed good crystallinity in single phase material, with lattice constant decreasing with increasing Mn concentration. Single phase AlMnN was found to be p type while AlMnN/AlMn mixed phase material was found to be highly conductive n type. Magnetization measurements performed with a superconducting quantum interference device magnetometer indicated fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 21 publications
1
49
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] In particular, Crdoped AlN is one of the most promising materials for practical applications in spin-dependent electronic devices because its Curie temperature has been reported to be above 900 K, which is the highest among III-nitrides. 8,[10][11][12][14][15][16] In the previous reports, the room-temperature ferromagnetism was observed in Cr-doped AlN films fabricated at various substrate temperatures by sputtering 10,15,16) and molecular beam epitaxy, 8,11,12,14) but their magnetic moments were different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] In particular, Crdoped AlN is one of the most promising materials for practical applications in spin-dependent electronic devices because its Curie temperature has been reported to be above 900 K, which is the highest among III-nitrides. 8,[10][11][12][14][15][16] In the previous reports, the room-temperature ferromagnetism was observed in Cr-doped AlN films fabricated at various substrate temperatures by sputtering 10,15,16) and molecular beam epitaxy, 8,11,12,14) but their magnetic moments were different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Following theoretical predictions, 3 many efforts have been made toward FS with high T C , and room-temperature ferromagnetism has been observed in doped oxides and nitrides, such as ZnO, 4 TiO 2 , 5 SnO 2 , 6 and GaN. 7 Recently high-temperature ferromagnetism has also been observed in AlN-based materials, [8][9][10][11][12][13] and T C of Cr-doped AlN has been reported to be over 900 K. 12,13 Different values of saturation moment were reported in the Cr-doped AlN films fabricated by sputtering, 8,12 molecular beam epitaxy, 9,13 and ion implantation, 10 suggesting that the magnetic properties may be sensitive to the film-growth conditions. Compared to the experimental progress, the theoretical understanding of the high-temperature ferromagnetism is still rather limited.…”
mentioning
confidence: 99%
“…The electron concentration and mobility are shown in the inset of tration is still as low as 10 17 cm −3 . The features of deep defect levels and low carrier densities in the AlCrN system make the carrier-mediated model of ferromagnetism unlikely for this material, 8,[11][12][13] since this theory requires high concentration of free carriers. 3,18,19 Although the nitrogen deficiency does not create significant numbers of free carriers, the induced defects and localized carriers may play a role in the ferromagnetism in AlCrN films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 For useful practical applications, ferromagnetism must be achieved above room temperature. Recent reports of room temperature ferromagnetism include Mn-GaN, 3 Mn-AlN, 4 Cr-GaN, 5 and Cr-AlN. 6 (Ga,Mn)N films grown by molecular beam epitaxy were reported to be ferromagnetic above room temperature, with a Curie temperature, T c , of 940 K. 7 Another study of the same system synthesized using solid-state diffusion reported a T c in the range of 220-370 K, 3 while bulk Cr-doped GaN fabricated using the sodium flux method was reported to have a T c of 280 K. 5 The search for the physical mechanism responsible for the observed ferromagnetic properties and the question of the applicability of the classical magnetic models have become topics of intense interest.…”
mentioning
confidence: 99%